2018
DOI: 10.1186/s12014-018-9194-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of serum proteins AHSG, FGA and APOA-I as diagnostic biomarkers for gastric cancer

Abstract: BackgroundThe development of clinically accessible biomarkers is critical for the early diagnosis of gastric cancer (GC) in patients. High-throughput proteomics techniques could not only effectively generate a serum peptide profile but also provide a new approach to identify potentially diagnostic and prognostic biomarkers for cancer patients.MethodsIn this study, we aim to identify potentially discriminating serum biomarkers for GC. In the discovery cohort, we screened potential biomarkers using magnetic-bead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Little is known about HIST1H2BK in previous cancer studies. For certain markers identified here, their potential for non-invasive cancer diagnosis has been reported previously, such as serum TIMP1 and FGA proteins used for the diagnosis of PDAC and gastric cancer, respectively 36–38. Collectively, these results suggested that plasma EVs contain a considerable number of exLRs that are potential biomarkers for PDAC detection.…”
Section: Discussionsupporting
confidence: 74%
“…Little is known about HIST1H2BK in previous cancer studies. For certain markers identified here, their potential for non-invasive cancer diagnosis has been reported previously, such as serum TIMP1 and FGA proteins used for the diagnosis of PDAC and gastric cancer, respectively 36–38. Collectively, these results suggested that plasma EVs contain a considerable number of exLRs that are potential biomarkers for PDAC detection.…”
Section: Discussionsupporting
confidence: 74%
“…For instance, Davalieva et al reported the non-invasive biomarkers in urine with higher specificity than prostate-specific antigen (PSA) in patients with prostate cancer; a number of genes, including FGG and FGA were observed to be present with different abundances, which could be potential biomarker candidates (41). In another study, the serum levels of the proteins, alpha 2-HS glycoprotein (AHSG), FGA and apolipoprotein A1 (APOA-I), were identified as diagnostic biomarkers for gastric cancer (GC); ELISA data suggested that the serum levels of FGA, AHSG and APOA-I in patients with GC differed significantly as compared to the healthy volunteers; moreover, the serum levels of these three proteins were associated with TNM stages and could reflect tumor burden (42). The FGG gene mediates the formation of the fibrinogen γ chain, a subunit of the fibrinogen protein.…”
Section: Discussionmentioning
confidence: 99%
“…SCML4 was reported to be downregulated in breast cancer stem cells (41). However, APOA2, NTRK2 , and FGA are oncogenes in PDAC, glioblastoma, and gastric cancer (4245). Thus, FTO may inhibit ICC progression by reducing oncogene expression ( TEAD2 and CMTM4 ) and inducing tumor suppressor expression ( HAO2, NR5A2, CCL19, TCF21, NTRK2 , and SCML4 ).…”
Section: Resultsmentioning
confidence: 99%